Anti-platelet activity of infusion of Tithonia diversifolia's leaves - Soares, V. C G; Baldissera, L.; Diz-Filho, E. B S; Antunes, E.; ToyamaM, M. H. [UNESP] (My University, 2012)
Tithonia diversifolia, also known as Mexican arnica, has been used in traditional medicine to treat inflammatory refractory with absence of citotoxicity. The possible health risks associated with the consumption of ingestion of the infusion (tea) plant makes it is necessary to identify the potential pharmacological activity or toxicity to prove certain plants that are acclimated in Brazil. Considering the limited number of pharmacological studies regarding the Tithonia diversifolia, the aim of this study was evaluate the effects of this infusion in platelet aggregation. Venous blood was collected with informed consent from healthy volunteers who denied taking any medication in the previous 14 days. Whole blood was transferred into polypropylene tubes containing one-tenth of final volume of acid citrate dextrose (ACD-C; citric acid 3%, trisodium citrate 4%, glucose 2%; 1:9 v/v) and centrifuged at 200g for 15 min. Platelet rich plasma was added of wash buffer solution (NaCl 140mM, KCl 5mM, sodium citrate 12mM, glucose 10mM and saccharose 12mM; pH 6; 5:7 v/v) and centrifuged at 800g for 12 min at 20°C. Platelet pellet was gently resuspended in Krebs-Ringer solution and counts were performed on a Neubauer chamber. Aggregation assay was carried out with 400 μL of platelet suspension (1.2x10 8 platelets/mL) in a cuvette at 37°C with constant stirring. Platelet suspension was incubated for 3 min with aqueous extract infusion (0.6-20μg/mL) prior to addition of thrombin (100 mU/mL). Percentage of platelet aggregation was recorded with an aggregometer (Chrono-log Lumi-Aggregometer model 560-Ca, USA). Our results show an inhibition of thrombin induced platelet aggregation in the presence of 0.6-20 ug/mL Tithonia diversifolia infusion leaves. The Tithonia diversifolia infusion leaves inhibits thrombin induced washed platelet aggregation.
Keywords: Aqueous extract; Platelet aggregation; Tithonia diversifolia; acid citrate dextrose; antithrombocytic agent; citrate sodium; glucose; plant extract; polypropylene; potassium chloride; sodium chloride; sucrose; thrombin; Tithonia diversifolia extract; unclassified drug; analytical equipment; antiplatelet activity; centrifugation; concentration response; drug activity; drug infusion; human; human cell; incubation time; informed consent; medicinal plant; pH; plant leaf; thrombocyte aggregation inhibition; thrombocyte count; thrombocyte rich plasma; venous blood